Health professionals and palliative care in pediatrics: a literature review (Research, Society and Development, 2023)
Introduction: One of the basic principles for child palliative care is care focused on the child, oriented to the whole family, built with a good team-family relationship. Therefore, the multidisciplinary team must be able to fully meet the needs of the child, enabling actions that guarantee a dignified survival and adequate control of the symptoms, understanding the patient and his family in their subjectivity and complexity. Objective: To analyze health professionals and palliative care in pediatrics through a literature review. Method: It was a systematic literature review with an exploratory and qualitative approach. Results: From the combination of descriptors, 117 studies were obtained. In an initial evaluation through the abstracts, it was found that 83 were outside the time frame, 21 did not answer the guiding question, therefore, 104 articles were excluded. It is possible to select 13 articles to compose the final sample of this bibliographic review. Conclusion: The significant contribution of health professionals in palliative care in pediatrics was verified in the analyzed studies. However, it was also noted that there is a need for more attention to the area in health centers and educational institutions, thus training professionals who are more qualified to deal with the context. Palliative care is of paramount importance in pediatrics, considering that dealing with terminally ill children represents, in the vast majority of cases, an impasse for the health team and family members, and studies are increasingly needed in order to deepen knowledge in this area.